The model of transformational leadership of teachers in higher vocational colleges in Heilongjiang province - Xu, Yanbin; Noichun, Nuntiya (Edelweiss Applied Science and Technology, 2025)
Effective leadership is pivotal in enhancing the quality and performance of educational institutions. The fast-paced development of industries, coupled with the need for skilled talent in Heilongjiang Province, necessitates the Transformational leadership model to ensure vocational colleges remain relevant and competitive. This study develops a transformational leadership model for teachers in higher vocational colleges in Heilongjiang Province of China, employing a mixed-methods approach to explore key leadership dimensions. We collected data from 504 survey respondents and 9 semi-structured interviews. Confirmatory factor analysis confirmed the model’s structural validity (CFI=0.965, RMSEA=0.041), while structural equation modeling supported all six hypotheses with significant path coefficients ranging from 0.72 to 0.80 (p<0.001). The second-order CFA further validated the framework, with path coefficients from 0.8333 to 0.9144, integrating Visionary Motivation, Individualized Consideration, Intellectual Stimulation, Industry-Education Collaboration Competency (IECC, β=0.72), Teaching Innovation Capability (TIC, β=0.79), and Teacher Professional Development (TPD, β=0.77). IECC and TIC emerged as critical dimensions, reflecting Heilongjiang’s need for industry-aligned teaching and digital innovation. This study advances transformational leadership theory by incorporating dimensions tailored to Heilongjiang’s vocational education context, addressing the region’s need for industry-aligned teaching.